Improved deep learning (inception) CNN for detecting small tectonic plates of broken Anatolian, Turkey - Shaheen Mohammed Saleh Ahmed; Hakan Guneyli (All Earth, 2021)
The Anatolian was at one time a single plate that is currently being turned into many small plates. The earliest separation stage occurred in the southeastern Anatolian from the Palaeocene to middle Eocene times. This study for the first time confirmed that the Anatolian plate was broken into a group of small tectonic plates with an area less than 1000 km2. We have called them nanoplates. We have detected formation of (9) nano plates in the East Anatolian region with (6) nanoplates in the West Anatolian region and single nanoplate in the central Anatolian region. The key geological feature that we targeted here to find these nano plate boundaries is the fault network. A network of deep fractures along the nano plates boundaries. This paper determined these boundaries by integrating and analysing huge remote sensing geophysical data. This paper ued for the first time the weights of filters in inception convolutional neural network (CNN) in Anaconda python Tensor Flow and Keras platform. Also used latest special scientific programming libraries of Python language like SciPy, Arcpy, NumPy and Pandas for data preparation. In addition, this study used ArcGis10.8 from ESRI foundation for GIS analysis beside PCI GEOMATICA 2020 for image analysis.